A visual bio-barcode immunoassay for sensitive detection of triazophos based on biochip silver staining signal amplification. (15th June 2021) - Wang, Yuanshang; Du, Pengfei; Abd El-Aty, A.M.; Chen, Ge; Jia, Huiyan; Cui, Xueyan; Oz, Emel; Zhang, Yudan; Zhang, Xiuyuan; Qin, Guoxin; Yan, Feiyan; Wang, Jing; et al.
Highlights: A novel and sensitive immunoassay was developed for detection of triazophos. Quantification was performed by immobilization of bio-barcodes by biochip modified capture probes. The method shows a good accuracy and correlated well with ELISA method. The developed method provides a promising visual detection system for trace detection of pesticide. Abstract: Herein, a novel visual method for detecting triazophos based on competitive bio-barcode immunoassay was described. The competitive immunoassay was established by gold nanoparticles (AuNPs), magnetic microparticle (MMPs) and triazophos, combined with biochip hybridization system to detect the residual of triazophos in water and apple. Because AuNPs carried many bio-barcodes, which hybridized with labeled DNA on the biochip, catalyzed signal amplification using silver staining was detected by grayscale values as well as the naked eye. Notably, the grayscale values decreases with increasing the concentrations of triazophos, and the color change weakened gradually. The detection range was in between 0.05 and 10 ng/mL and the minimum detection limit was set at 0.04 ng/mL. Percent recovery calculated from spiked water and apple samples ranged between 55.4 and 107.8% with relative standard deviations (RSDs) of 12.4–24.9%. It has therefore been shown that this protocol provides a new insight for rapid detection of small molecule pesticides in various matrices.